PENGEMBANGAN MATERI TENTANG KECEMASAN SISWA SMA/SEDERAJAT - Arifah, Nurul; Yakub, Elni; ', Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Students are not only learning to get student achievement, but alsolearning to deal with or overcome the various problems.. For example the issue of thecommunication anxiety and anxiety to face the exam. Therefore, the researchers need todevelop a material about the student anxiety in the schools. This research is expected tobe used by guidance and counseling teachersto solve the student’s problems. Thismaterial is prepared using research and development (R & D) methods. The purposesare 1)Establishment of appropriate materials about student anxiety of SMA. 2) Todetermine the quality of the student anxiety materials. This material had validated bytwo supervisors, guidance and counseling teacher, and for students of SMA. Thismaterial is tested in 4 lessonhours time (4 x 45minutes). This material consists of asense of anxiety, characteristics of anxiety, factors affecting anxiety, symptoms ofanxiety, the sense of anxiety communication, the characteristics of anxietycommunication, factors that influence the anxiety of communication, how to overcomeanxiety communication. The results of the development of this material indicates thequality of the material produced is in “Very Good” category, with the acquisition score4.2 for all aspects of assessment.Keywords: Development of guidance counseling materials, student anxiety